Heat Tolerance in Donkeys and Mules - Pal, Yash; Gupta, Ashok K; Yadav, M P (Annals of Arid Zone, 2016)
Heat tolerance in adult indigenous donkeys, exotic donkeys (Poitu) andmules was studied for exposure to direct sun during hot dry period. There wereno inherent differences in the rectal temperature and respiratory frequency undershade in the three breeds. Eight hours of exposure daily for six consecutive dayscaused a significant (P